Government Communication Model in Strengthening Village Institutions in Bertah Village, North Sumatra - Besti Rohana Simbolon; Doli Tua Mulia Raja Panjaitan; Piki Darma Kristian Pardede (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2022)
Based on Government Regulation Number 8 of 2016 concerning the Second Amendment to Government Regulation Number 60 of 2014 concerning Village Funds from the State Budget (APBN), village funds must be managed in an orderly, obedient, efficient, economical, effective, transparent and responsible manner by paying attention to the sense of justice and propriety and prioritizing the interests of the local community. Therefore, it is important to strengthen village institutions and village officials, so that they are qualified and empowered to carry out development. Indonesia has a total of 83,820 villages which need to be assisted so that the disbursed village funds are not wasted. This study uses a qualitative grounded theory approach by observing, interviewing 30 informants and analyzing village documents. The results of the study found that the human resource factor of the village head as a communicator, was more trusted by village institutions and the community because of his open, democratic communication style, willingness to accept suggestions/opinions and  empathy  according to the equalitarian style and the relinquishing  style of communication. The government communication model in strengthening village institutions is a mentoring model where communication starts from regency and district. However, the strengthening has not been seen optimally because of the high dependence of village institutions and village officials on village heads and village assistants so that they are less independent. The use of messages is more face-to-face, using messages and WhatsApp with information functions that are more persuasive and educative.